1978
DOI: 10.1038/bjc.1978.115
|View full text |Cite
|
Sign up to set email alerts
|

Antigen shedding by human breast-cancer cells in vitro and in vivo

Abstract: Summary.-Human breast cancer cells were adapted to chemically defined medium in order to recover naturally shed glycoproteins. Sephadex G-150 chromatography of these glycoproteins revealed 1 major and 2 minor peaks. When the cells were grown in the presence of 3H-leucine, the radioactive shed proteins had a Sephadex profile identical to the unlabelled shed glycoproteins. PAGE analysis of these proteins showed 5 major bands. Antigenically similar proteins were found in the serum of female nude mice bearing BOT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In parallel with this, we have previously reported that NSCLC tumors express significant levels of the immunomodulatory cytokines, IL-1 receptor antagonist and IL-10 [38,39]. This phenomenon, combined with the shedding of soluble tumor-speci®c antigens [2,10,30,31] and reduced cell-surface expression of class I MHC antigens [9,43], may provide the tumor with a defense against immune surveillance.…”
Section: Discussionmentioning
confidence: 81%
“…In parallel with this, we have previously reported that NSCLC tumors express significant levels of the immunomodulatory cytokines, IL-1 receptor antagonist and IL-10 [38,39]. This phenomenon, combined with the shedding of soluble tumor-speci®c antigens [2,10,30,31] and reduced cell-surface expression of class I MHC antigens [9,43], may provide the tumor with a defense against immune surveillance.…”
Section: Discussionmentioning
confidence: 81%
“…that the rate of turnover of tumor cell membrane antigens is related to the biological behavior of the tumor in vivo, particularly its immunogenicity and capacity for metastasis [12,13]. Tumor cells with metastatic capacities have been shown to shed glycoproteins from the cell surface into the host circulation [3,14] and to possess a greatly accelerated glycoprotein metabolism [4].…”
Section: Rat Hepatic (H) and Tumor (T) Cells The Cell Surface Of Thementioning
confidence: 99%
“…These antigens are glycoproteins or whole plasma membrane fragments (De Broe et al, 1977) which circulate in a free state or complex with host immunoglobulins (Sjogren et al, 1971;Bowen et al, 1975). Although a number of groups have demonstrated the release of human and animal cell-surface proteins into the serum of tumour-bearing animals (Jamasbi et al, 1978;Nordquist et al, 1978; Rao & Bonavida, 1977;Primus et al, 1976) a study of this process is complicated by the host's immune system.…”
mentioning
confidence: 99%